The Impact of Government Assistance to State-owned Enterprises on Foreign Start-ups: Evidence from Yangtze River Delta - Omar Abu Risha; Qingshi Wang; Shanshan Dou; Mohammed Ismail Alhussam; Junguo Shi (East Asian Economic Review (EAER), 2022)
Different types of corporate ownership may affect the environment among firms and could influence the decisions of new entities in the region. This study determines the role of state-owned enterprises (SOEs) in hindering new foreign manufacturing firms in the Yangtze River delta (YRD). The negative binomial regression is used for city-sector level data and the following points summarize the results: Firstly, the unique privileges that SOEs enjoy alongside governmental support create difficulties for foreign firms trying to establish themselves near existing SOEs. Secondly, although core cities are more attractive to foreign firms than peripheral cities, the role of core-periphery reveals that, in spite of all the regional advantages core cities could offer, whenever the share of SOEs is higher, the core-periphery system will have an adverse impact on new foreign firms. In other words, government preference for SOEs can suppress the attraction of foreign startups. However, after 2008, the governmental authorities finally succeeded in implementing their promising policy of fair treatment and competition in only the core cities.
Keywords: F23; H79; L60; 330; New Foreign Firms; State-owned Enterprises; Core–periphery; Yangtze River Delta